Perencanaan Struktur Gedung Pendidikan Pesantren Muhammadyah Boarding School (MBS) Yogyakarta - Ilham, Ilham (JOURNAL OF APPLIED SCIENCE (JAPPS), 2024)
The structural planning of the Muhammadiyah Islamic Boarding School (MBS) campus is part of efforts to develop safe, comfortable, and sustainable educational facilities. This community service activity aims to design building structures that meet the school's technical standards and functional needs. The methods used in this project include site surveys, soil condition analysis, structural modeling, and consultation with relevant stakeholders. The planning results include selecting the optimal structural system based on load analysis and soil-bearing capacity. The building structure uses an appropriate foundation system, a reinforced concrete framework for ultimate strength, and an efficient roof system to support thermal comfort. Structural analysis was carried out using ETABS software to ensure stability and resistance to dead loads, live loads, earthquake loads, and wind loads. The conclusion of this project shows that the structural planning in the form of upper and lower structure design drawings (Foundations) of the Muhammadiyah Islamic Boarding School campus has met safety standards, cost efficiency, and sustainability principles. This building is a reinforced concrete structure with concrete quality fc' 25 MPa referring to SNI 2847-2019, the structural system used is the Special Moment Resisting Frame System (SRPMK). This is expected to be a solid foundation in the construction stage and contribute to improving the quality of education in the school environment